2003
DOI: 10.1063/1.1632025
|View full text |Cite
|
Sign up to set email alerts
|

Polarized organic electroluminescence: Ordering from the top

Abstract: Effective ionic charge polarization using typical supporting electrolyte and charge injection phenomena in molecularly doped polymer light-emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…A number of reports demonstrate polarized electroluminescence (EL) with the aim of incorporating such polymer LEDs as backlights into liquid crystal displays. 18 For instance, cyanobiphenyl liquid crystals can be aligned by rubbing polyimide and thus to have dichroic ratios in absorption spectra. 19 The frequently used materials are polyacrylate, 20,21 polyfluorene, 18,[22][23][24][25][26][27][28] and their oligomer derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports demonstrate polarized electroluminescence (EL) with the aim of incorporating such polymer LEDs as backlights into liquid crystal displays. 18 For instance, cyanobiphenyl liquid crystals can be aligned by rubbing polyimide and thus to have dichroic ratios in absorption spectra. 19 The frequently used materials are polyacrylate, 20,21 polyfluorene, 18,[22][23][24][25][26][27][28] and their oligomer derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…18 For instance, cyanobiphenyl liquid crystals can be aligned by rubbing polyimide and thus to have dichroic ratios in absorption spectra. 19 The frequently used materials are polyacrylate, 20,21 polyfluorene, 18,[22][23][24][25][26][27][28] and their oligomer derivatives. 29 Additionally, lyotropic liquid crystals, which possess a hexagonal mesophase to solubilize the monomer and direct its electropolymerization, are utilized to prepare poly-(3,4-ethylenedioxythiophene) (PEDOT) films that replicate the texture and birefringence of the LC template.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, the patterning of conjugated polymers itself has emerged as a new class of research topics, 15,16 in which the polymers are regarded as functional materials, such as light emitter. Reproducible micro-or nanopatterning of conjugated polymers is now of importance for applications, such as a microlaser, 4,7,9,11 photonic crystal, 17 nanoscale OLEDs, 18 quantum dots, 19 etc. The downsizing of the patterned conjugated polymers has advantages, such as improvement of light trapping in polymer photodiode, 20 increase in efficiency, and control of polarity and spectrum of emission from microstructured OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The emission color of PFs also can be tuned to be green, yellow, red, and so forth by incorporating narrow‐band gap comonomers into the polymer backbone or other chemical modification 7–9. In addition, many PF derivatives exhibit thermotropic liquid crystalline properties, which is another important property of PFs and have remarkably potential application for PLEDs 10–14. On the one hand, the PL and EL properties from light‐emitting polymer films can be enhanced by forming liquid crystalline domains inside the film via thermal annealing at nematic‐isotropic phase transition temperature (TNI) without employing additional photonic structures 15.…”
Section: Introductionmentioning
confidence: 99%
“…Since Grell et al reported liquid crystalline properties of PF for the first time,19 many blue‐light‐emitting PF derivatives have been found in a liquid crystalline (LC) state and undergo phase changes under thermal treatments rendering facile overall alignment, which can be applied for linearly polarized light 11–13, 20. However, very few green‐ or white‐light‐emitting PF derivatives with liquid crystalline properties have been explored.…”
Section: Introductionmentioning
confidence: 99%